E-Learning Utilization for English Teaching in the Midts of Pandemic - Nurbianta Nurbianta (Universitas Muhammadiyah Lampung, 2021)
Everybody knows the dangers of the Corona Virus Disaster 2019 (Covid-19). The grip of Covid-19 in the world has frightened many people and has also led to many significant transitions, including in the education field. The existence of Covid-19 has caused the mode of learning to change. Therefore we need technology that can be used as a learning medium to achieve effective & efficient learning. In this research, researchers used E-Learning such as zoom, google class, WhatsApp, and telegram as transmitter tools in students' teaching process at SMK Integral Hidayatullah Berau. This research was a quantitative study, and the design was descriptive quantitative, the sample size was 31 students of the eleventh grade at SMK Integral Hidayatullah Berau. The research instrument was a test, and the statistical tools used to analyze the data were the mean, median, mode. Furthermore, the research results that focus on the implementation of E-Learning in teaching English were outstanding. In other words, the use of E-learning was beneficial to gain effectiveness and efficiency in teaching English.